Remediation of antimony-contaminated soil using food waste organic fertilizer and rhizosphere microbial response mechanism - Luo, Shenglian; Ouyang, Yingxuan; Zeng, Weimin; Wu, Xiaoyan (Frontiers in Microbiology, 2025)
Antimony pollution poses a significant threat to both the ecological environment and the health of people living in mining regions. Using organic fertilizers is an efficient approach for the remediation of heavy metal contamination in soil. This study aimed to explore how food waste organic fertilizer (FF) can remediate antimony-contaminated soil and the associated rhizosphere microbial response mechanism. The analysis of soil physicochemical properties revealed that the application of FF notably reduced bulk density (from 1.57 to 1.08 g cm−3), enhanced salinization levels, and increased the content of organic matter, available nitrogen, phosphorus, and potassium (p < 0.05). In the FF group, the plant height of Pteris vittate increased by 82.12% compared to the control group. The antimony valence state analysis revealed that after applying FF, the Sb(III) content in the rhizosphere and endosphere of P. vittate was significantly lower than that in other groups (p < 0.05), while the Sb(V) content in the endosphere was the highest. This indicated that FF can enhance the oxidation and detoxification of Sb(III) in the soil to produce Sb(V), which is then accumulated in the root of P. vittate. Microbial community analysis showed that the application of FF promoted the continuous enrichment of Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes in the roots of P. vittate; this is particularly evident in the specific microbial groups with Sb(III) oxidation, nitrogen fixation, and phosphorus and potassium solubilization functions, including Acinetobacter, Sphingomonas, Comamonas, Bradyrhizobium, Alphaproteobacteria, Acidovorax, and Paenibacillaceae. These microbes help mitigate the adverse effects of poor soil conditions and heavy metals on the growth of P. vittate in mines. This study provides a new approach to resource utilization of food waste and the remediation of antimony-contaminated sites.